Synthetic cannabinoids awareness among patients with opioid use disorder in Serbia – A survey based cross-sectional pilot study - Mijatović Jovin, Vesna; Dickov, Isidora; Ratković, Dragana; Dickov, Aleksandra; Tomas, Ana (Frontiers in Psychiatry, 2023)
Introduction There is limited data on the awareness and use of synthetic cannabinoids (SCs) in high-risk population in Serbia, despite SCs becoming more and more common at illicit drug market. Aim This pilot study aimed to examine the awareness on SCs of patients with an opioid-use disorder and to identify patient characteristics and other factors associated with SCs use. Patients and methods Survey was conducted at the Clinic for Psychiatry, Clinical Center Vojvodina, Serbia. Participants were the patients hospitalized due to the treatment of opioid dependence. Results Out of 64 patients (median age 36.37 years), one third (32.81%) reported using SCs. Socio-demographic characteristics of the subjects were not associated with SCs use. There were differences in the most common sources of information reported between the SCs users and non-users. Majority of SCs users (76.0%) were informed about SCs through friends, compared with just 26.0% of non-users (<0.001). Nearly all study participants (93.8%) were daily tobacco users. The share of respondents reporting alcohol and marihuana use was significantly higher among the SCs users (52.0% vs. 20.9%, p=0.011 and 15.6% vs. 12.5%, p=0.015, respectively Higher share of SCs users used multiple psychoactive substances (38.1% vs. 16.3%), and this difference was statistically significant as well (p=0.047)). The most reported adverse effect of SCs among users included dry mouth (81.0%), trouble thinking clearly (52.4%) and panic attack (52.4%). Conclusion . Findings can serve as a basis for more effective prevention and harm reduction within this vulnerable marginalized population.